ANALISIS PENGELOLAAN SAMPAH ORGANIK PASAR LASI TRADISIONAL DI KECAMATAN CANDUANG KABUPATEN AGAM - Fatma, Fitria (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Objective: To analyze the management of organic waste in canduang lasi market.Background: Market problems garbage a matter authentic to followed up. Waste disposala market is cleaned to waters are behind market. Menwhile, the water used for the needs ofvernacular by the people residing around these waters. So that the water tained bygarbage and gives rise to surrounding air pollution settlement.Introduction: Traditional lasi market is located in east the capital of kabupaten agam ± 73km. the community canduang generally derive their main income farmers 75% of thepopulation. Land the farm plant vegetables and sugar case that require fertilizer in theagricultural sector. Market lasi many sell vegerables, so many the production and garbageorganic. Trash managed well, so that the community throw garbage into the waters behindmarket. The river or these waters flowing in the middle settlement.Methods: this study adopted qualitative approaches descriptive in nature, namely explainthe phenomena in depth through data collection.Results and Discussion: The result of components input is system management the marketis not formed in the marketlasi, so that funds, human resources and infrastructure no filled.System management process of waste in the trash using the sacks pouch collection,transportation, processing not done by the merchants and the community around lasimarket. And final discharge garbage done captivity in waters back market.Conclusion: System patients outside the organization as well as the work program of atthe port authority had been formed to be carried out efficiently, only market many humanbeings and lasi who as not yet been, so the program of doing the government bidding itwill not stand garbage management and those bylaws organic lasi market.Keywords: Organic garbage, compost, traditional markets